Comparison of single never-married women at different contexts - Pourasad Shahrak, Shakiba; Brand, Serge; Taghizadeh, Ziba (Advances in Nursing & Midwifery, 2024)
Context: In traditional communities, marriage is recognized as a mandatory requirement to having children and to achieving social status; given this context, singleness may unfavorably impact an individual’s psychological well-being. This holds particularly true for women. The purpose of the present review was to compare the single never-married women status in Western and Eastern societies. Evidence Acquisition: Published data were gathered from PubMed, Google Scholar, Web of Science, and Iranian databases such as SID and Magiran. The keywords included “psychological health”, “social health”, “reproductive health”, “marriage”, “never-married women”, “singleness”, and “single women”. Databases were searched with no time limitation and in both Persian and English languages. Results: Being single, particularly in old ages, has a variety of adverse psychological consequences in individuals, families, and communities, including depression, strained interpersonal relationships, isolation, rejection, sadness, and anxiety. Some outcomes are common, while others vary according to different cultures and religions, such as response to sexual needs. Conclusions: Singleness have positive and negative effects on individuals. The mental burdens of singleness affect persons, families, and societies. Cultural and societal peculiarities define the way how to cope with the effects of singleness. Thus, identifying the social and psychological consequences of singleness and planning to address them in accordance with the cultures and religions can be an important step for improving the well-being of never-married women.